Angular vs. circular: the role of shapes on food packaging graphics in purchase intentions, perceived healthiness, and self-construal - Liang, Shichang; Zhou, Yizheng; Qin, Qiuju; Zhang, Xiaochuan; Li, Junrong; Zhang, Tingting; Li, Jingyi; Zhu, Miao (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study investigates the effect of shapes in food packaging graphics (SFPG) on consumer purchase intentions. While prior research has primarily focused on cross-modal associations between SFPG and other sensory modalities (e.g., taste, smell), the direct influence of SFPG on purchase behavior remains underexplored.MethodsThree experiments were conducted to examine how SFPG influences perceived healthiness and purchase intentions. Experiment 1 compared the effects of angular vs. circular SFPG on consumer purchase intentions. Experiment 2 tested the mediating role of perceived healthiness in this relationship. Experiment 3 explored the moderating effect of self-construal (independent vs. interdependent) on the SFPG-purchase intention link.ResultsResults from Experiment 1 revealed that angular SFPG significantly enhanced purchase intentions compared to circular SFPG. In Experiment 2, perceived healthiness was found to mediate the relationship between SFPG and purchase intentions. Experiment 3 demonstrated that self-construal moderated the effect of SFPG on purchase intentions. Specifically, angular SFPG increased purchase intentions for individuals with an independent self-construal, whereas circular SFPG had a more significant effect for individuals with an interdependent self-construal. Additionally, the study rules out alternative explanations of visual salience.DiscussionThese findings offer a new perspective on how SFPG influences consumer decision-making, highlighting the role of perceived healthiness and self-construal in shaping purchase intentions. The results provide valuable implications for food packaging design and help businesses better position their products in the market and attract their target consumers.